The well‐being and mental health of doctoral candidates. (24th June 2022) - Kismihók, Gábor; McCashin, Darragh; Mol, Stefan T.; Cahill, Brian
Abstract: After a long period of relative neglect, the mental well‐being and the mental health of researchers and employees in academia are increasingly entering the limelight. The growing body of evidence suggests that a high number of doctoral researchers work under elevated levels of stress and frustration, and that this has a significant impact not only on their personal health and research output, but also on their future career development. In this paper, therefore, we first discuss what a dystopian and a utopian learning journey of early career researchers may look like from a well‐being perspective. Subsequently, and based on extensive dialogues with more than 250 researchers and professionals active in the researcher mental health domain, we highlight a number of key focal points that both early career researchers, their supervisors, and institutions alike should consider when it comes to planning and delivering mental health oriented educational activities for doctoral researchers.